The Influence of Self-Efficacy and Work Input on Physical Education Teachers’ Creative Teaching - Xiong, Yan; Sun, Xi-Yang; Liu, Xue-Qian; Wang, Ping; Zheng, Bing (Frontiers in Psychology, 2020)
Objectives: To explore the influence of different background factors on middle school physical education teachers' self-efficacy, work input and creative teaching, and to reveal the relationship between teaching self-efficacy and work input on creative teaching. Methods: By means of self-efficacy, work input and creative teaching scale, a questionnaire survey was conducted among middle school physical education teachers, and the data were processed and modeled by SPSS and AMOS statistical analysis software. Results: 1) Physical education teachers' self-teaching effectiveness was influenced by background factors such as gender, age, teaching age, full-time or part-time work and educational level. Work input was only affected by age, teaching experience and educational level, while creative teaching seemed to be only related to background factors such as educational background and full-time or part-time work; 2) physical education teachers' general teaching effectiveness and personal teaching effectiveness had significant positive effects on energy input, concentration input, dedication input, cognitive creativity, skill creativity and emotional creativity; 3) concentration input had a significant positive impact on the three-dimensional of creative teaching, while energy input and dedication input had no impact on the three-dimensional of creative teaching and 4) work input as an intermediary variable of self-efficacy's influence on creative teaching had been verified, but the real intermediary role was not the whole work input, but the concentration input in its structure. Conclusion: Both general and individual teaching effectiveness had positive effects on work input and creative teaching, but the energetic and dedicated input in work input cannot promote teachers' creative teaching effectively. Therefore, the professional ethics training of physical education teachers in their enthusiasm and dedication to work should be strengthened.